Growth performance and nutrient digestibility of broiler chicken fed with organic acid blends at different levels of dietary crude protein - Ang, S. K.; Loh, Tech Chwen; Kok, P. C. (2009)
Organic and inorganic acid blends (OAB) are known for their antibacterial properties and also as growth promoters in diets of livestock and poultry. However, the effect of OAB on digestibility of nutrients in the diet is still unknown. The objectives of this study were to investigate the effects of feeding OAB on the growth performance and digestibility of nutrients fed at different concentrations of crude protein in the starter and finisher diets of broilers. A total of 336 day old Cobb chicks placed in 24 cages were used. Fourteen birds were placed in each cage during the starter period; whereas 10 birds were placed in each cage during the finisher period. The chicks were obtained from a local commercial hatchery. All the birds were wing banded for identification purposes and all birds were weighed individually. The experiment was conducted for 42 days. Starter diet was offered from day old until day 21, whereas finisher diet was offered from days 22 to 42. The feed and water were provided ad-libitum. The OAB (OrgacidsTM) was supplemented at 1.5kg per ton of feed as recommended by the manufacturer (Sunzen Biotech Corporation). The feed was formulated to be isocaloric with different levels of crude protein. The amino acid level was similar for all the treatment groups. Titanium oxide (TiO2) at 0.3% was added in all the diets as an indigestible indicator in order to calculate the digestibility of nutrients at the end of third and final week of rearing. These birds were allocated into 4 dietary groups: (i) CON: Starter 22% CP; Finisher 19% CP; (ii) T1:Starter 22% CP + OAB; Finisher 19% CP + OAB; (iii) T2: Starter 20% CP; Finisher 18% and (iv) T3:Starter 20% CP + OAB; Finisher 18% + OAB. There were no significant differences (P>0.05) between treatments for body weight, live weight gain, feed intake, growth rate and feed conversion ratio. Crude protein digestibility was not significantly different (P>0.05) between treatments. However, birds fed with non-OAB had slightly poorer digestibility compared to OAB fed birds. The birds fed non-OAB diets also had lower (P<0.05) apparent digestibility of phosphorus than the OAB fed birds. The apparent digestibility of phosphorus for T1 and T3 was not significantly different (P>0.05). The apparent digestibility of calcium for T3 was significantly higher (P<0.05) than the CON and T1. No significant results (P>0.05) were found between T2 and T3, and between CON, T1 and T2.